Tourist tax and ratings of online reviews - Antonio Marsi; Emanuela Randon (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2021)
Tourist taxes represent one of the principal sources of revenue for a number of local authorities. Using a dataset of more than 300 thousands reviews on TripAdvisor, we analyze the effect of tourist taxes on online ratings posted by hotel costumers. Online ratings are strategic variables for the competitiveness of hotels and local destinations and so the assessment of the impact of tourist taxes on online reviews is important to design suitable strategies and policies both for firms and local municipalities. We show that the share of complaints about the tax increases with the tax rate, but the relationship gets weaker as the hotel quality increases, suggesting that low-quality costumers are more sensitive to tax increases. Tax mentioning reviews have on average a 20% lower rating and this difference becomes smaller and not significant for high quality hotels. We disentangle the different sources of complaining, finding that the lack of information and the cash payments weight more negatively on the average rating (respectively less 27% and 21%). Using a random-effects logit model we show that what matters for costumers is the percentage tax on the room price and not the absolute amount of the legal tax rates based on the hotel stars. This effect is present only for hotel stays with an average double room price under 100 Euros. Our results provide public authorities with useful suggestions to change the actual tax system by setting the tourist tax as an ad valorem tax on room price and assessing optimal tax rates accordingly to their incidence on the price of the stay.
Keywords: D12; H21; H22; L83; Z3; 330; Tourism Tax; Online Ratings; Tax Incidence